Strategi Pengembangan Ekowisata Air Berkelanjutan Danau Sipin Kota Jambi - Margono Margono; Suandi Suandi; Syafri Syafri (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Tourism is one of the industries that has been developed in many countries as a source of state/regional income, as well as for employment and improving the quality of life of the local community. Tourist destinations are built using various approaches, which aim to become attractive tourist objects. as many domestic and foreign tourists. Sipin Lake is located in the Telanaipura District, precisely in the Legok Village. The Sipin Lake area has a length of about 4,500 meters and an average width of more than 300 meters with a lake depth of 2-6 meters. This study aims to describe the activities of Sipin Lake Water Ecotourism in Jambi City, to find out the aspects that influence the development of Sipin Lake Sustainable Water Ecotourism in Jambi City, and develop strategies that can be applied in the development of Sipin Lake Sustainable Water Ecotourism in Jambi City. The locations used as research sites were Legok Village and Sungai Putri Village with data collection methods in the form of observation (questionnaire) and interviews with the community and stakeholders. The results of data processing used descriptive quantitative methods, namely SWOT analysis and Rapfish analysis. In determining the strategy using the SWOT analysis, the position of the matrix is obtained in quadrant I (+,+) by establishing a strategy of strengths (S) and opportunities (O), namely support and commitment from the Jambi City Government, involving the Lake Sipin community and conducting community empowerment such as traditional snacks. , souvenirs and cafes, followed by the availability of sanitation-based facilities (clean water, public toilets/toilets, waste water management and self-supporting community waste management, for example TPS3R). Adding entertainment facilities for the community when traveling to Lake Sipin, such as jogging tracks, decorative armchairs, skaterboard tracks, pedestrian parks, hut restaurants and selfie spots. The results of the Rapfish analysis, that Sipin Lake Water ecotourism on ecological aspects, economic aspects and social aspects get less sustainable values for current conditions. So it is necessary to make efforts on these 3 aspects so that they are mutually sustainable, in order to achieve sustainable ecotourism